2003
DOI: 10.1038/sj.onc.1206805
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor overexpression and autocrine loop in breast cancer cells

Abstract: We show here that nerve growth factor (NGF), the canonical neurotrophic factor, is synthesized and released by breast cancer cells. High levels of NGF transcript and protein were detected in breast cancer cells by reverse transcription-PCR, Western blotting, ELISA assay and immunohistochemistry. Conversely, NGF production could not be detected in normal breast epithelial cells at either the transcriptional or protein level. Confocal analysis indicated the presence of NGF within classical secretion vesicles. Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
100
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 37 publications
11
100
1
1
Order By: Relevance
“…However, among 41 patients of their study, nearly half of them had adenocarcinoma, thus number of OESCC patients is much lower than our study, which might lead to insufficient evaluation. On the contrary, as our results, most of previous reports regarding other cancers have shown the positive relationship between malignant potential of tumours and expression of NGF or its receptors (Geldof et al, 1998;Schneider et al, 2001;Zhu et al, 2001Zhu et al, , 2002Sakamoto et al, 2001a, b;Kishibe et al, 2002;Davidson et al, 2003;Dolle et al, 2003).…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…However, among 41 patients of their study, nearly half of them had adenocarcinoma, thus number of OESCC patients is much lower than our study, which might lead to insufficient evaluation. On the contrary, as our results, most of previous reports regarding other cancers have shown the positive relationship between malignant potential of tumours and expression of NGF or its receptors (Geldof et al, 1998;Schneider et al, 2001;Zhu et al, 2001Zhu et al, , 2002Sakamoto et al, 2001a, b;Kishibe et al, 2002;Davidson et al, 2003;Dolle et al, 2003).…”
Section: Discussioncontrasting
confidence: 52%
“…These are compatible with our clinical findings from more than 100 cases of immunohistochemistry that overexpression of NGF is associated with lymph node metastasis and associated with poorer clinical outcome. To our knowledge, this is the first time to demonstrate NGF autocrine secretion in gastrointestinal cancer, although several previous studies have shown NGF autocrine secretion in other types of cancer (Weeraratna et al, 2000;Zhu et al, 2001Zhu et al, , 2002Dolle et al, 2003), as well as in noncancerous tissues (Torcia et al, 1996;Pincelli and Marconi, 2000).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations